Thermal Comfort in Humid Tropical Climate Areas (Case Study on Open Spaces and Shaded Spaces in Medan City) - Agus Jhonson Sitorus; Dicky Andrea Sembiring; Wahyu Abdillah; Devin Defriza Harisdani (International Journal of Architecture and Urbanism, 2023)
Humid tropical climates are areas with high humidity temperature characteristics. This high temperature is partly due to sunlight which is always constant throughout the day, while high humidity is usually associated with relatively high rainfall. Because of this, in general, buildings in this area have a fairly wide canopy or what is often referred to as a shading element in architecture. This will ultimately affect the thermal comfort of buildings in the humid tropics. In this study the authors tried to look at the two main factors that shape thermal comfort, namely the level of temperature and humidity. The author will compare three types of outdoor spaces, namely sheltered outdoor spaces with walls on one side, shaded rooms without walls and outdoor spaces without shade. The research was conducted by measuring temperature and humidity simultaneously at the three locations. Measurements were carried out for two weeks, at five different times with an interval of two hours. The results obtained show that there are significant differences in temperature and humidity between open spaces and shaded spaces. Where the shaded room has lower temperature and humidity. As for other shaded rooms, it is known that shaded rooms without walls have lower temperature and humidity.